Adaptation and co‐adaptation of skin pigmentation and vitamin D genes in native Americans. Issue 4 (15th December 2020) - Missaggia, Bruna Oliveira; Reales, Guillermo; Cybis, Gabriela B.; Hünemeier, Tábita; Bortolini, Maria Cátira
Abstract: We carried out an exhaustive review regarding human skin color variation and how much it may be related to vitamin D metabolism and other photosensitive molecules. We discuss evolutionary contexts that modulate this variability and hypotheses postulated to explain them; for example, a small amount of melanin in the skin facilitates vitamin D production, making it advantageous to have fair skin in an environment with little radiation incidence. In contrast, more melanin protects folate from degradation in an environment with a high incidence of radiation. Some Native American populations have a skin color at odds with what would be expected for the amount of radiation in the environment in which they live, a finding challenging the so‐called "vitamin D–folate hypothesis." Since food is also a source of vitamin D, dietary habits should also be considered. Here we argue that a gene network approach provides tools to explain this phenomenon since it indicates potential alleles co‐evolving in a compensatory way. We identified alleles of the vitamin D metabolism and pigmentation pathways segregated together, but in different proportions, in agriculturalists and hunter‐gatherers. Finally, we highlight how an evolutionary approach can be useful to understand current topics of medical interest.